Actin and α-actinin orchestrate the assembly and maturation of nascent adhesions in a myosin II motor-independent manner - Choi, Colin K. (2008)
Using two-colour imaging and high resolution TIRF microscopy, we investigated the assembly and maturation of nascent adhesions in migrating cells. We show that nascent adhesions assemble and are stable within the lamellipodium. The assembly is independent of myosin II but its rate is proportional to the protrusion rate and requires actin polymerization. At the lamellipodium back, the nascent adhesions either disassemble or mature through growth and elongation. Maturation occurs along an α-actinin–actin template that elongates centripetally from nascent adhesions. α-Actinin mediates the formation of the template and organization of adhesions associated with actin filaments, suggesting that actin crosslinking has a major role in this process. Adhesion maturation also requires myosin II. Rescue of a myosin IIA knockdown with an actin-bound but motor-inhibited mutant of myosin IIA shows that the actin crosslinking function of myosin II mediates initial adhesion maturation. From these studies, we have developed a model for adhesion assembly that clarifies the relative contributions of myosin II and actin polymerization and organization.